2001
DOI: 10.1007/bf02322050
|View full text |Cite
|
Sign up to set email alerts
|

Impaired autonomic control of heart rate and blood pressure in obesity: role of age and of insulin-resistance

Abstract: The objectives of this study were to investigate cardiac and peripheral autonomic nervous system changes in normotensive overweight or obese subjects and the possible relation between these changes and insulin resistance independent of age. The authors used spectral analysis to measure simultaneously the short-term variability of heart rate (HR) and blood pressure (BP) using a Finapres device, in 67 normotensive overweight or obese patients (age 37 +/- 12 y, body mass index [BMI] = 37 +/- 9 kg/m2) and 45 never… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
27
1
2

Year Published

2005
2005
2016
2016

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(32 citation statements)
references
References 52 publications
1
27
1
2
Order By: Relevance
“…Both obesity and hyperinsulinemia (4,6,25,26) have been shown to cause alterations in HRV, however, the potential additive effects are unknown and differences between obese women with and without type 2 diabetes are not clear. Consistent with earlier findings (4), we observed that sympathovagal balance (Ln LF/HF) is higher in obese women than in non-obese women, but there was no difference between the obese women with and without type 2 diabetes.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Both obesity and hyperinsulinemia (4,6,25,26) have been shown to cause alterations in HRV, however, the potential additive effects are unknown and differences between obese women with and without type 2 diabetes are not clear. Consistent with earlier findings (4), we observed that sympathovagal balance (Ln LF/HF) is higher in obese women than in non-obese women, but there was no difference between the obese women with and without type 2 diabetes.…”
Section: Discussionmentioning
confidence: 99%
“…The very low frequency (VLF) power was obtained for the region below 0.040 Hz and was subtracted from the total power when the data were normalized. Sympathetic modulation of the heart has been associated with the LF spontaneous oscillations of the spectral period (24), whereas the HF component has been shown to be primarily influenced by the efferent vagal activity (6). As an indirect measure of sympathovagal balance the LF/HF ratio has been used.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…From our previous reports [21][22][23][24][25][26][27] , low preheparin LPL mass could be consistent with increased insulin resistance. It is known that the sympathetic nerve is activated under the condition of insulin resistance [31][32][33][34] and that blood vessels contract by activation of the sympathetic nerve. So, it is expected that the tonus of the sympathetic nerve in patients with systolic hypertension might be higher than that in patients with non-systolic hypertension before benidipine hydrochloride administration, because preheparin LPL mass levels were significantly lower in patients with systolic hypertension than in patients with nonsystolic hypertension before benidipine hydrochloride administration.…”
Section: Discussionmentioning
confidence: 99%
“…While the sympathetic activation is demonstrated at the level of the kidneys and skeletal muscles, cardiac sympathetic activity does not seem to be increased 11 . However, cardiac autonomic disturbances such as decreased vagal tonus, with or without sympathetic activation, are documented in obesity 12 .…”
Section: Introductionmentioning
confidence: 99%